MANAJEMEN PEMBERDAYAAN GURU DI MTS AL-ULUM MEDAN - amri susanto (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
ABSTRACT Qualitative research terms with titles “Empowerment of Teachers in MTs Al-Ulum Medan”. The purpose of this study was to determine (1) Management Planning Teacher Empowerment in Mts Al-Ulum Medan (2) Empowerment of Teachers in MTs. Al-Ulum (3) Execution Management Teacher Empowerment in MTs Al-Ulum Medan (4) Evaluation of Teacher Empowerment Management at MTs Al-Ulum Medan.Method research approach is qualitative field research is to determine the empowerment of teachers in MTs Al-Ulum.The data were obtained through observation, interviews and documentation. In the observational study, the researcher know each activity while in the field and get accurate information about all objects. Subsequently, researcher conducted interviews with principals, administrators and teachers, to prepare research instruments such questions-written questions and alternative answers. Then the researcher to document the form of text and images and works of achievement and data schedule school discipline teaching and learning activities of the school. Furthermore, researcher studied all the events that took place during the researcher conducting the study.Results of this research can be concluded that the planning, organizing, implementation and supervision in MTs Al-Ulum has fulfilled the good empowerment management, with emphasis on the concept of Islam. Key Word: management planning teacher, empowerment of teacher, execution management teacher, evaluation of teacher,